A CORRELATION BETWEEN VOCABULARY MASTERY AND STUDENTS’ READING COMPREHENSION ( A Study to the Grade XII Students of SMA Negeri 1 Padang Bolak) - Sari Septiani Raya (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The objectives of this research are to know whether there is any significant correlation between vocabulary mastery and students’ reading comprehension at the grade XII students of SMA Negeri 1 Padang Bolak.This research uses descriptive method with pre-test post-test design. The population is all of the twelve grade students which consist of 4 classes with 135 students.Technique sampling that used on this research is simple random sampling and the number of the sample consists of 34 students. In collecting the data, the researcher uses multiple choice test to get the data of the students’ vocabulary mastery and reading comprehension. The researcher uses statistical analysis, the formula that will be used is Pearson formula (correlation of Product Moment). Based on the data analysis, it is found that that rxy (the correlation between x variable and y variable) was 0.363 and rt (r table) product moment df as number (N-nr = 34-2 = 32) is known that there was not number 32 in the table at interval 5%. So, the writer takes the nearest number and it is number 30, it is 0.349. It shows that rxy > rt (0.363 > 0.349). It means there is a significant correlation between vocabulary mastery and reading comprehension at the XII grade students of SMA Negeri 1 Padang Bolak.